Retaining Homeless Veterans in Outpatient Care: A Pilot Study of Mobile Phone Text Message Appointment Reminders - McInnes, D. Keith (American Public Health Association, 2014)
Objectives. We examined the feasibility of using mobile phone text messaging with homeless veterans to increase their engagement in care and reduce appointment no-shows. Methods. We sent 2 text message reminders to participants (n = 20) before each of their outpatient appointments at an urban Veterans Affairs medical center. Evaluation included pre- and postsurvey questionnaires, open-ended questions, and review of medical records. We estimated costs and savings of large-scale implementation. Results. Participants were satisfied with the text-messaging intervention, had very few technical difficulties, and were interested in continuing. Patient-cancelled visits and no-shows trended downward from 53 to 37 and from 31 to 25, respectively. Participants also experienced a statistically significant reduction in emergency department visits, from 15 to 5 (difference of 10; 95% confidence interval [CI]  = 2.2, 17.8; P = .01), and a borderline significant reduction in hospitalizations, from 3 to 0 (difference of 3; 95% CI = −0.4, 6.4; P = .08). Conclusions. Text message reminders are a feasible means of reaching homeless veterans, and users consider it acceptable and useful. Implementation may reduce missed visits and emergency department use, and thus produce substantial cost savings.